2011
DOI: 10.1080/10781911003769165
|View full text |Cite
|
Sign up to set email alerts
|

Taking back our streets: A clinical model for empowering urban youths through participation in peace promotion.

Abstract: A three-stage empowerment model is developed based on the experience of a psychotherapy group conducted with Black and Latino youth residents in an urban housing project with high rates of community violence. The model aims to not only ameliorate mental health symptoms related to exposure to community violence, but also enhance youths' ability to transform their sociocultural context through peace promotion. The three stages are (a) addressing chief complaints and symptom reduction, (b) exploring narratives, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Another goal in the therapy room becomes creating a space in which the complexity of social identity is explored. La Roche and Tawa (2011) suggested that an important piece of healing clinical symptoms related to racial discrimination involves youths examining their narrative for personal and cultural expectations as well as learning to resist and combat negative racial stereotypes that may contribute to misinterpretations of their own experiences. Introducing or talking about the historical and contemporary realities (i.e., using BHK) that inform clients' lived experiences and feelings can support the process of personal growth.…”
Section: Applications Of Black History Knowledge Model For Coping Andmentioning
confidence: 99%
“…Another goal in the therapy room becomes creating a space in which the complexity of social identity is explored. La Roche and Tawa (2011) suggested that an important piece of healing clinical symptoms related to racial discrimination involves youths examining their narrative for personal and cultural expectations as well as learning to resist and combat negative racial stereotypes that may contribute to misinterpretations of their own experiences. Introducing or talking about the historical and contemporary realities (i.e., using BHK) that inform clients' lived experiences and feelings can support the process of personal growth.…”
Section: Applications Of Black History Knowledge Model For Coping Andmentioning
confidence: 99%
“…The authors not only recognized the historical and contextual contours of their participants’ lives at the beginning of the articles, or offered somewhat more in the remainder of the study, they sustained their attention on the manifestations of structural and physical violence stemming from past and current racism. For example, this occurred in research conducted on Ugandan children (Mayengo et al, 2018), on how Whites perceived Black South African protestors during the #FeesMustFall movement (Kiguwa & Ally, 2018), and on a program targeting Black and Latino/a teenagers from violent communities (La Roche & Tawa, 2011). The other 11 studies comprise the special issue on the Apartheid Archive Project by South African researchers.…”
Section: Resultsmentioning
confidence: 99%
“…At the core of their study’s findings, the authors revealed language in which associations of savagery were used to reinforce institutional practices of symbolic violence against the students. Although the Kiguwa and Ally (2018) study entailed no contact with participants, La Roche and Tawa (2011) included close involvement with the research participants. The authors engaged the participants throughout a process that eventually yielded a community action project that was initiated by the youth, Black and Latino students who were also seen in therapy for the problems they experienced as resulting from violence.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations